2014
DOI: 10.1371/journal.pone.0108308
|View full text |Cite
|
Sign up to set email alerts
|

You Seem Certain but You Were Wrong Before: Developmental Change in Preschoolers’ Relative Trust in Accurate versus Confident Speakers

Abstract: The present study tested how preschoolers weigh two important cues to a person’s credibility, namely prior accuracy and confidence, when deciding what to learn and believe. Four- and 5-year-olds (N = 96) preferred to believe information provided by a confident rather than hesitant individual; however, when confidence conflicted with accuracy, preschoolers increasingly favored information from the previously accurate but hesitant individual as they aged. These findings reveal an important developmental progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 23 publications
(30 reference statements)
4
35
0
Order By: Relevance
“…The notion that children are promiscuously credulous to those around them has been disproved by ample evidence suggesting the ways in which dubious social signifiers and poor past performance may render a social communicator suspect and their assertions about the world regarded with scepticism [12, 13]. Epistemic vigilance is a necessary tool to protect against misinformation, whether as a consequence of malicious intent or incompetence on the part of the communicator [4].…”
Section: Introductionmentioning
confidence: 99%
“…The notion that children are promiscuously credulous to those around them has been disproved by ample evidence suggesting the ways in which dubious social signifiers and poor past performance may render a social communicator suspect and their assertions about the world regarded with scepticism [12, 13]. Epistemic vigilance is a necessary tool to protect against misinformation, whether as a consequence of malicious intent or incompetence on the part of the communicator [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although Ms. Flávia's reinforcement of the more accurate informant's responses was removed in Experiment 2, children proved sensitive to the plausible indices of knowledge versus ignorance displayed by the two informants and responded in a selective fashion during test trials, as shown in Figure . Although a great deal of research on selective trust has examined children's sensitivity to accurate naming (Harris, Koenig, Corriveau, & Jaswal, ), the present results confirm and extend those earlier results (Brosseau‐Liard et al ., ; Tenney et al ., ) by showing that young children are sensitive to other plausible indices of knowledge versus ignorance, notably confident naming as compared to hesitant silence. Admittedly, children could not check the accuracy of the names produced by the apparently well‐informed individual for the unfamiliar animals.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that children ranging from 4 to 6 years are sensitive to other potential indices of how informed or knowledgeable an informant is. In particular, even in the absence of objective indices of informant accuracy, they favour an informant who provides information with confidence rather than hesitation (Tenney, Small, Kondrad, Jaswal, & Spelman, ) and judge such an informant to be ‘smarter’ (Brosseau‐Liard, Cassels, & Birch, ). Hence, children are likely to prefer an apparently well‐informed individual who produces names for familiar and unfamiliar animals rather than an apparently less‐informed individual who names familiar animals but hesitates to produce names for unfamiliar animals.…”
Section: Discussionmentioning
confidence: 99%
“…Children do not always blindly trust others as reliable sources of information. Indeed, they evaluate potential sources on a wide range of behaviours and characteristics: whether someone has been accurate (Koenig & Harris, ), confident (Brosseau‐Liard, Cassels, & Birch, ), or has had good intentions (Liu, Vanderbilt, & Heyman, ; Mascaro & Sperber, ) all affect children's trust. Although children are clearly sensitive to some characteristics that are good indicators of whether someone will be a reliable source of information (i.e., whether someone has been accurate or not in the past), they also take note of more superficial traits that are less likely to be associated with reliability in their everyday lives.…”
Section: Introductionmentioning
confidence: 99%